2018
DOI: 10.1016/j.hpb.2018.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of postoperative pancreatic fistula rates using the updated 2016 International Study Group Pancreatic Fistula definition in patients undergoing pancreatic resection with soft and hard pancreatic texture

Abstract: The reported POPF rates may be used in planning future prospective studies. A widely accepted definition of PT is lacking and a correlation with the risk of POPF is based on subjective evaluation, which is still acceptable. Classification of PT into 2-groups is more reasonable than classification into 3-groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
69
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(91 citation statements)
references
References 121 publications
9
69
0
3
Order By: Relevance
“…Postoperative pancreatic fistulas (POPF) are present in 11%‐16% of cases. They account for most of the complications and usually are treated conservatively …”
Section: Introductionmentioning
confidence: 99%
“…Postoperative pancreatic fistulas (POPF) are present in 11%‐16% of cases. They account for most of the complications and usually are treated conservatively …”
Section: Introductionmentioning
confidence: 99%
“…Of all the risk factors for POPF, a soft consistency of the pancreatic parenchyma is one of the factors that is the most widely accepted [30,31,[37][38][39][40][41]. Eschmuminov et al [33] analyzed 22,376 patients included in 122 studies using the updated 2016 ISGPS (International Study Group Pancreatic Fistula) definition. They reported that the POPF rate was significantly higher in soft pancreas than in hard pancreas (RR, 4.4, 3.3 to 6,1; p < 0.001; n = 6393).…”
Section: Discussionmentioning
confidence: 99%
“…Several reasons have been proposed to explain the higher frequency of POPF in soft pancreas. Firstly, soft pancreas is likely to have a pancreatic duct with an average diameter less than 3 mm [33]. Secondly, soft pancreas has a higher exocrine function than hard pancreas and thus may produce more enzyme-rich pancreatic juice [31,42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This systematic review was conducted according to the PRISMA statement . A systematic literature search of the databases Cochrane, Embase, Medline, PubMed, and Scopus was conducted on 23rd of May, 2017, including only publications in English.…”
Section: Methodsmentioning
confidence: 99%